Modeling of Common Mode Interference of Secondary Side of Potential Transformer in VFTO Excitation - PANG Fubin, JI Jianfei, WU Xianqiang, ZHOU Mengxia, YAN Wei, XU Dong (Shanghai Jiaotong Daxue xuebao, 2025)
Very fast transient overvoltage (VFTO) is generated during the operation of isolation switches and circuit breakers in substations, which can affect the safe and reliable operation of power secondary equipment through cable transmission and spatial radiation. VFTO is a type of transient interference pulse which contains multiple frequency band interference components with frequencies reaching to 100 MHz. However, it is difficult to describe the time-frequency characteristics of VFTO interference waveforms by current electromagnetic interference models and experimental standards. Therefore, first, the generation mechanism and transmission path of VFTO in substations are analyzed and a measurement method for VFTO in substations is proposed. Macro and micro pulses of VFTO are measured on the secondary side of voltage transformers during isolation switch operation. Then, a method for the time-frequency characteristic analysis of VFTO is proposed based on synchronous compressed wavelet transform, which can obtain the time-frequency characteristics of VFTO and improve the time-domain and frequency-domain resolution. Finally, a VFTO interference model for substation is established based on attenuated damping oscillation waves and a method for extracting the model parameters is proposed based on difference evolutionary algorithm. The experimental results show that predictions made by the model are basically consistent with the measured results with a coefficient of determination (R2) is 0.85. The proposed model can describe the time-frequency characteristics of VFTO interference waveforms, providing a basis for the development of VFTO immunity standards and the operation and maintenance of power equipment.